2021
DOI: 10.1123/jcsp.2020-0055
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Life in Sweden During the COVID-19 Pandemic

Abstract: Sweden has adopted a somewhat different approach to handle the corona pandemic, which has been widely debated both on national and international levels. The Swedish model involves more individual responsibility and reliance on voluntary civic liability than law enforcement, while common measures in other countries are based on more controlling strategies, such as restrictive lockdowns, quarantines, closed borders, and mandatory behavior constraints. This commentary aims to give a brief overview of the foundati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Sweden's strategy to manage the spread of Covid-19 has not included any form of lockdown, in contrast to the approaches adopted by most other countries. Instead, Sweden's strategy has been largely based on strong recommendations for society such as encouraging people who can work from home to do so, and recommending that people minimise their number of social contacts ( Weman Josefsson, 2021 ). Until the summer of 2020, primary schools and day-care centres had not been required to close, neither had shops nor restaurants as long as guidelines were followed.…”
Section: Introductionmentioning
confidence: 99%
“…Sweden's strategy to manage the spread of Covid-19 has not included any form of lockdown, in contrast to the approaches adopted by most other countries. Instead, Sweden's strategy has been largely based on strong recommendations for society such as encouraging people who can work from home to do so, and recommending that people minimise their number of social contacts ( Weman Josefsson, 2021 ). Until the summer of 2020, primary schools and day-care centres had not been required to close, neither had shops nor restaurants as long as guidelines were followed.…”
Section: Introductionmentioning
confidence: 99%
“…In the post-COVID-19 era, travel will continue to play an important role in stress reduction, socialisation processes, and the reinforcement of interpersonal relationships, but the exploration of local recreational options will be prioritised, as proven by the research of Steen Jacobsen et al (2021) [26] through the territorial example of the metropolis of Oslo. The research of Weman-Josefsson (2021) [27] also confirms the market penetration of the staycation: 86% of the Swedish population reported that in 2020 they spent their summer vacation domestically, at a destination close to their home, instead of previously preferred destinations. With the gradual return of the demand for international travel, personal safety and the health safety status of touristic destinations (which have been increasingly important factors even before the pandemic) are becoming top factors in destination choices.…”
Section: Safe and Secure Travelingmentioning
confidence: 81%
“…In classical music, a musician is defined as professional if he/she is trained at music college and established to some degree at the (professional) institutions or the free cultural life. The Swedish strategy to deal with the pandemic did stand out internationally, not applying a lockdown in the strict sense, but using recommendations to affect behaviours (stay at home, keep a distance) ( Weman Josefsson, 2021 ). As the numbers of deceased and infected persons in Sweden were high, society was marked by precautions and many people chose to isolate themselves and limit social interactions ( Jukkala et al, 2021 ).…”
Section: Context: Working As a Freelance Musician In Swedenmentioning
confidence: 99%